Inter-European cooperation in the field of combating and solving transnational crimes - Voroņins, Kirills (Riga Graduate School of Law, 2023)
The main purpose of this study is to challenge the legal possibilities and potential of the EU law enforcement structures in the field of ensuring collective security and combating crimes in the territory of the European Union. The primary problem of this study is the ability to correctly assess the effectiveness of existing mechanisms and methods of cooperation between law enforcement structures of the European Union, as well as their compliance with the current realities and needs of the EU countries and their security in general. The end of this study can be considered a positive or negative verdict regarding the effectiveness of the current legal and factual system of cooperation between law enforcement agencies of the European Union in the field of combating transnational crimes.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Research Subject Categories::LAW/JURISPRUDENCE::Procedural law::Criminal procedure; Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; transnational crimes